One-step fabrication of silica colloidosomes with in situ drug encapsulation. Issue 113 (28th November 2016) - Su, Yechao; Zhao, Hong; Wu, Jinrong; Xu, Jianhong
Abstract : In situ modification, drug encapsulation and fabrication of hollow silica colloidosomes in microfluidic device. Abstract : Colloidosome is an important field of microencapsulation with various applications in catalysis, the food industry and pharmacy. Owing to its outstanding biocompatibility, silica colloidosomes are promising for biomedical applications. Nevertheless, silica modification as well as drug encapsulation are separated in some reported fabrication methods. In this article, bio-friendly materials SiO2 nanoparticles and chitosan are used in fabrication as dispersants. Pickering emulsion formed under the shear force of continuous phase n -octanol was further solidified and freeze-dried to obtain silica colloidosomes. In situ covalent modification of SiO2 nanoparticles' hydrophobicity by chitosan is the key to the formation of hollow silica colloidosomes and drug encapsulation can also be achieved during emulsion formation. By tuning the size of SiO2 nanoparticles and the solidification time of chitosan the size of interstices on the surface can be easily controlled to realize different release profiles of encapsulated drugs.